Risk assessment of osteoporosis in pre- and postmenopausal periodontally healthy and chronic periodontitis women with digital panoramic radiographs - Rajashri Abhay Kolte; Abhay Pandurang Kolte; Anushree Manohar Potey (Wolters Kluwer Medknow Publications, 2017)
Background: Osteoporosis is particularly high in females, the early identification of which remains a challenge. Panoramic radiographs are routinely advised to detect periodontal diseases and can be used to predict low bone mineral density (BMD). Hence, this investigation was aimed to identify the risk of osteoporosis in pre- and postmenopausal periodontally healthy and chronic periodontitis women with digital panoramic radiographs. Materials and Methods: The study population consisted of 120 patients equally divided as Group I - Premenopausal periodontally healthy, Group II - Premenopausal periodontitis, Group III - Postmenopausal periodontally healthy, and Group IV - Postmenopausal periodontitis. Clinical parameters were recorded, and digital panoramic radiographs were used to record the mental index (MI), panoramic mandibular index (PMI), and mandibular cortical index (MCI) scores. Results: MI was found to be varied, and the differences were highly significant among Group III and IV (P = 0.0003) and Group II and IV (P = 0.0007), and significant difference was found between Group I and Group II (P = 0.0113). MCI evaluation showed a greater prevalence of C2 and C3 patterns among postmenopausal women. MCI correlation with MI (P < 0.0001), PMI (P < 0.0001) and age (P = 0.0029) indicated a highly significant variance. Conclusion: The positive association between MCI and chronic periodontitis in postmenopausal women confirms the high risk of osteoporosis in them. Furthermore, an increased percentage of patients with undetected decrease in BMD may be identified by screening with digital panoramic radiographs which are done on a routine basis for periodontal and other dental diseases and thus could be used as an effective aid to quantify bone density in future.